2008
DOI: 10.1007/s11104-008-9832-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water table on greenhouse gas emissions from peatland mesocosms

Abstract: This version available at http://nora.nerc.ac.uk/5459/ NERC has developed NORA to enable users to access research outputs wholly or partially funded by NERC. Copyright and other rights for material on this site are retained by the authors and/or other rights owners. Users should read the terms and conditions of use of this material at http://nora.nerc.ac.uk/policies.html#access This document is the author's final manuscript version of the journal article, incorporating any revisions agreed during the peer revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
98
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 58 publications
(57 reference statements)
18
98
5
Order By: Relevance
“…This finding contradicts previous research on peatlands [16], but is consistent with the findings of Bubier et al [21]. Currently, no study has reached a clear conclusion about how rewetting affects CH 4 emissions.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This finding contradicts previous research on peatlands [16], but is consistent with the findings of Bubier et al [21]. Currently, no study has reached a clear conclusion about how rewetting affects CH 4 emissions.…”
Section: Resultssupporting
confidence: 71%
“…The drop in the water Researchers have drawn different conclusions about the effects of alternate drying and rewetting on CO2 release from the soil in wetlands. Some studies suggested that alternate drying and rewetting can stimulate CO2 release from peatlands as a result of increased substrate availability to microbes from the release of osmolytes accumulated during the drying phase, as well as cell lysis and the breakdown of aggregates that release previously protected organic matter [4,16]. In our study, alternate drying and rewetting had little impact on CO2 release.…”
Section: Resultscontrasting
confidence: 40%
“…Mesocosms are considered as an effective system for measuring the effects of climate change on carbon emissions, especially when simulating changes in water table levels and temperature (Dinsmore et al, 2009a;Strack and Waddington, 2007;Updegraff et al, 2001). Although mesocosms allow easy control of water table levels, this experimental system can also give biased estimates of carbon emission.…”
Section: Mesocosm Studies and Their Limitationsmentioning
confidence: 99%
“…Higher environmental temperatures may accelerate decomposition and oxidize the surrounding peat in the cylinder, thereby releasing more carbon. Second, the death of plant roots cut during mesocosm collection may accelerate mineralization (Dinsmore et al, 2009a), leading in turn to higher carbon emissions during early stages of experiments. Third, a decrease in water content in surface peat and an increase in soil aeration may stimulate decomposition in the short term (Strakova, 2010).…”
Section: Mesocosm Studies and Their Limitationsmentioning
confidence: 99%
See 1 more Smart Citation